2014
DOI: 10.1016/j.bbamcr.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the biogenesis of OXPHOS complexes in cell transition from replicating to quiescent state

Abstract: A study is presented on the expression of mitochondrial oxidative phosphorylation complexes in exponentially growing and serum-starved, quiescent human fibroblast cultures. The functional levels of respiratory complexes I and III and complex V (adenosine triphosphate (ATP) synthase) were found to be severely depressed in serum-starved fibroblasts. The depression of oxidative phosphorylation system (OXPHOS) complexes was associated with reduced levels of peroxisome proliferator-activated receptor gamma coactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…However, no evidence has been shown that these kinases phosphorylate ATP synthase. It has been suggested that protein kinase A regulates ATP synthase by phosphorylating the cAMP response element (CREB) and activating the expression of the PGC-1␣ gene, implying that protein kinase A regulates ATP synthase at the transcriptional rather than the posttranslational level (37). Nevertheless, the presence of numerous phosphorylation motifs on ATP synthase subunits suggests that this complex can be regulated through phosphorylation by several different kinases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, no evidence has been shown that these kinases phosphorylate ATP synthase. It has been suggested that protein kinase A regulates ATP synthase by phosphorylating the cAMP response element (CREB) and activating the expression of the PGC-1␣ gene, implying that protein kinase A regulates ATP synthase at the transcriptional rather than the posttranslational level (37). Nevertheless, the presence of numerous phosphorylation motifs on ATP synthase subunits suggests that this complex can be regulated through phosphorylation by several different kinases.…”
Section: Discussionmentioning
confidence: 97%
“…Also, due to phosphate instability, the nature and length of tryptic digests, and 70% coverage sequence of this protein, some phosphorylations, including PKC-␣-mediated phosphorylation, could have been missed. Scansite analysis predicted classic PKC isozymes to phosphorylate Thr 27 , Ser 37 , and Ser 47 localized to the terminal ␣-helix of the ␥-subunit, but phosphoproteomic analysis did not recover terminal peptides containing these amino acids. However, this terminal ␣-helix is present in the vertical shaft surrounded by ␣-and ␤-subunits, making the access of a kinase to the peptide rather difficult.…”
mentioning
confidence: 99%
“…Strickingly, therapy-naïve AML cells expressing high levels of CD39 also exhibited a significantly higher ex vivo EC 50 for AraC compared to the CD39 low subpopulation (Fig.1I). On the other hand, residual AML cells derived from AraC-treated mice exhibited a lower basal sensitivity to the cytotoxic drug independent of the level of CD39 expression ( Fig.1I).…”
Section: Enhanced Cd39/entpd1 Expression and Activity Are Involved Inmentioning
confidence: 96%
“…Impaired mitochondrial energy metabolism, oxidative stress conditions and age-related progressive accumulation of oxidatively damaged and misfolded proteins, which in turn aggregate and impair cellular house keeping and specialized functions, all together contribute to PD pathogenesis [45,46]. All this supports an adjuvant therapeutical action of natural antioxidant phenols (see the case of resveratrol [44] and hydroxytyrosol [47]) which can promote the expression and/or the activity of gene products involved in cell energy metabolism and protection against oxidative stress and productions/accumulation of oxidized/misfolded proteins [48,49]. In this respect the neuropeptide CART (cocaine-amphetamine-regulated transcript)which is mainly expressed in the brain, particularly in dopaminergic midbrain regions, and has antioxidant activities, qualifies as another therapeutic candidate for PD [50,51].…”
Section: More Molecular Targets For Pd Therapymentioning
confidence: 99%